2009
DOI: 10.2478/v10063-008-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Titania deposits on nanosilicas

Abstract: Titania (content C TiO2 = 2.7-20.0 wt%) was synthesized on different fumed silica substrates (A-50, A-100, A-380) using Ti[OCH(CH 3 ) 2 ] 4 as a precursor interacting with silica/adsorbed water in 2-propanol or CCl 4 medium, dried and then heated at 1073 K for 1 h. Initial and pretreated nanosilicas and titania/silicas were studied using XRD, adsorption, FTIR, TEM, AFM, and TPD-MS methods. The morphology of grafted titania (anatase/rutile/amorphous phase composition, particle size distribution, aggregation, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…The ATR-FTIR spectra are consistent with the XRD and TEM results [ 40 ] revealing that the particulate morphology of titania correspond to crystalline anatase. In the case of ST20, the titania particles ranged between 15 and 20 nm.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The ATR-FTIR spectra are consistent with the XRD and TEM results [ 40 ] revealing that the particulate morphology of titania correspond to crystalline anatase. In the case of ST20, the titania particles ranged between 15 and 20 nm.…”
Section: Resultssupporting
confidence: 84%
“…It was found that titania grafted onto silica A-50 is characterized by much lower crystallinity than titania synthesized alone because of silica inhibitory effects [ 40 ]. Modification of ST20 by sodium alginate can change diffusion of adsorbate into pores (voids) and provide a possibility for further surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…The total pore volume V p was evaluated from the nitrogen adsorption at p/p 0 = 0.98-0.99 (p and p 0 denote the equilibrium pressure and the saturation pressure of nitrogen at 77.4 K, respectively). The nitrogen desorption data [25] were used to compute pore size distributions (PSDs) (differential f V (R p ) ~ d V p /dR p and f S (R p ) ~ dS/dR p ) using a regularization procedure [26] under non-negativity condition (f V (R p ) 0 at any R p ), at a fixed regularization parameter = 0.01, with a model of voids between spherical nanoparticles packed in random aggregates (V model) with a self-consistent regularization (SCR) procedure [27,28]. The differential distribution functions f V (R p ) ( f V (R p )dR p ~ V p ) were converted to incremental PSD (IPSD, (R p ) at i (R p ) ~ V p ).…”
Section: Methodsmentioning
confidence: 99%